Integrating network pharmacology, molecular docking and experimental verification to reveal the mechanism of artesunate in inhibiting choroidal melanoma - Ma, Qing-yue; Liu, Yi-chong; Zhang, Qian; Yi, Wen-dan; Sun, Ying; Gao, Xiao-di; Zhao, Xin-tong; Wang, Hao-wen; Lei, Ke; Luo, Wen-juan (Frontiers in Pharmacology, 2024)
Background: Artesunate (ART) from Artemisia annua shows potential in treating various tumors, including choroidal melanoma (CM), a malignant ocular tumor with poor prognosis and limited treatment options. Methods: Potential ART targets were identified using PubChem, Swiss Target Prediction and TCMSP databases. CM-related genes were selected from OMIM, GeneCards and DisGeNET databases. Intersection targets underwent PPI network analysis and GO/KEGG pathway analysis. Molecular docking predicted ART-target interactions. ART's effects on CM were evaluated through CCK8, colony formation, transwell, flow cytometry and Western blot assays. In vivo assays on subcutaneous tumors in nude mice validated ART's effects. Results: Network pharmacology identified key pathways and core targets for ART in CM treatment. Molecular docking confirmed strong ART-target binding. In vitro assays showed ART inhibited CM cell proliferation and migration by promoting apoptosis via the p53 pathway, causing cell cycle arrest at G0/G1 by inhibiting PI3K/AKT/mTOR and increasing ROS via the NRF2/HO-1 pathway. In vivo assays confirmed ART's anti-proliferative effects on CM. Conclusion: ART demonstrated significant anti-cancer effects on CM by promoting apoptosis, inducing cell cycle arrest and increasing ROS levels, suggesting therapeutic potential for CM.